"News Is About What Happens on the Inside"—News in an Informal Urban Settlement in South Africa. Issue 4 (2nd October 2019) - Leal, Suzette
Abstract: The news industry foregrounds the affluent and the middle class who have the means to financially benefit the for-profit business. Embedded in this commercial approach are theories determining news values and reasons for news media consumption (uses and gratifications). These tools are, however, not necessarily relevant to financially disadvantaged individuals— those who cannot afford mass media news, who struggle to relate to content crafted around the elite, and whose physical immobility detaches them from the rest of society. South Africa has a significant number of people affected by poverty. The aim of this qualitative study was thus to explore the applicability of news theory to residents of an informal urban settlement in Gauteng—Pango Camp. The findings highlight that conventional news values and uses and gratifications do not "automatically" apply to the poor or marginalised. In fact, this community differentiates between "inside" and "outside" news with a preference for the former, despite abundant opportunities to engage with mass media ("outside") news. Consequently, the community's inward focus results in segregation and isolation from mainstream information. Furthermore, participants' sporadic news media engagement is predominantly out of habit and boredom and not borne out of a desire for surveillance of the environment.